Staging Islam in England drama and culture, 1640-1685 - Birchwood, Matthew (Boydell & Brewer, 2008)
'This stimulating book will be welcomed by historians, literary scholars, and anyone interested in the history of the English fascination with Islam and the cultural exoticism associated with the East.' PROFESSOR GERALD MACLEAN. Transmitted via the mechanisms of trade and diplomacy and reflected through stage and press, England's cultural encounters with Islam - its peoples, its history, its territories - were fundamental to the ways in which the nation constructed itself through all the tribulations of the seventeenth century; a preoccupation with Islam permeated religious, political, diplomatic and commercial discourses to a degree that has not been recognised by standard accounts of the period. This book traces engagement with Islam in English political and dramatic life from the inauguration of the Long Parliament until the death of Charles II. It explores the reception and representation of Islam in a wide range of English writings of the period, employing close textual and historical research to trace the development of the 'Turk' from the archetype of cruelty and treachery to the complex and often contradictory figure of mid-century discourse. Throughout, it argues that Islam provided a repository of meanings ripe for transposition to Revolutionary and Restoration England, a process that transfigured the 'East' through the lens of English politics and vice-versa